MENENTUKAN PERPANGKATAN MATRIKS TANPA MENGGUNAKAN EIGENVALUE - Rini Pratiwi; Rolan Pane; Asli Sirait (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This paper discusses an algorithm to determine the power of a square matrix, A , without computing its eigenvalues. The algorithm can be used to compute An, for each real number n which is greater or equal to two.